2021
DOI: 10.47608/jki.v14i22020.159-167
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Covid-19 on Hotel Industry In Asian Countries

Abstract: The spread of Covid-19 has led to a global problem in all aspects of life, including in the tourism sector that directly affects the hotel industry. Asia as a continent with many countries that rely most of their revenue on tourism suffers a severe blow. The purpose of this study was to investigate the impacts of the novel Covid-19 on the hotel industry in Asian countries. Through a descriptive qualitative method, the researchers collected data from journals, research reports, books, government documents, arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…The argument that needs to be built regarding the impact of Covid-19 that has spread to the existence of the tourism industry applies to what is highlighted by Agustina and Yosintha (2021). In Asia, comparison with other regions such as Africa, Australia, Europe, and America is in a more severe trend.…”
Section: Discussionmentioning
confidence: 99%
“…The argument that needs to be built regarding the impact of Covid-19 that has spread to the existence of the tourism industry applies to what is highlighted by Agustina and Yosintha (2021). In Asia, comparison with other regions such as Africa, Australia, Europe, and America is in a more severe trend.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have conducted studies to examine the effects of COVID-19 on the tourism sector. [6] used a qualitative descriptive method to investigate the impacts of COVID-19 on the hotel industry in Asian countries. It found that because of the cancelation of domestic and international airlines to China, the hotel occupancy rate has declined by 75% from January 14 in 2020.…”
Section: Pandemic Uncertainty and Tourism Sectormentioning
confidence: 99%
“…Hal ini disampaikan oleh Sekretaris Jenderal PHRI, bahwa sejak wabah dimulai pada awal Januari, tingkat hunian keseluruhan negara telah anjlok menjadi 30% hingga 40%. Dibandingkan dengan musim sepi reguler yang dapat mencapai hingga 50%-60%, beberapa hotel bahkan turun hingga 20% setelah Indonesia mengumumkan kasus COVID-19 pertamanya pada 2 Maret 2020 (Agustina & Yosintha, 2020). Selama masa pandemi, sektor pariwisata diperkirakan akan terus mengalami penurunan bila pemerintah Indonesia tetap memberlakukan kebijakan PSBB.…”
Section: Hasilunclassified